Genome-Wide Identification and Expression Analysis of the MADS-Box Gene Family in Sweet Potato [Ipomoea batatas (L.) Lam] - Shao, Zhengwei; He, Minhong; Zeng, Zhipeng; Chen, Yanzhu; Hanna, Amoanimaa-Dede; Zhu, Hongbo (Frontiers in Genetics, 2021)
MADS-box gene is a class of transcription factors widely present in eukaryotes, which is one of the largest transcription factor families in plants. It plays an important role in plant growth and development, and participates in the growth and development of flowers and fruits. Sweet potato is the seventh most important food crop in the world. It’s tuberous root, stems and leaves contain a large number of proteins, lipids, carotenoids, anthocyanins, conjugated phenolic acids and minerals, which has high edible, forage and medicinal value, and is also an important energy crop. MADS-box gene family is rarely reported in sweet potato for now, and its function and mechanism need to be studied. In this study, we performed a comprehensive analysis of MADS-box genes in the sweet potato genome, identified 95 sweet potato MADS-box genes, analyzed the phylogenetic relationship and subfamily distribution with Arabidopsis MADS-box genes. Chromosomal localization indicated an unequal number of MADS-box genes in all 14 chromosomes except LG3. The MADS domain and K domain of the sweet potato MADS-box genes were identified by motif analysis. We identified 19 MADS-box genes with collinear relationships and analyzed duplication events. Cis-acting elements, such as a light-responsive element, auxin-responsive element, drought-inducible element, and MeJA-responsive element, were found in the promoter region of the MADS-box gene in sweet potato. Transcriptome sequencing found 34 genes and highly expressed in sweet potato flowers and fruits, and 19 genes highly expressed in tuberous root, pencil root or fibrous root. qRT-PCR again validated the expression levels of the 10 genes and found that IbMADS1, IbMADS18, IbMADS19, IbMADS79, IbMADS90 were highly expressed in tuberous root or fiberous root, and IbMADS18, IbMADS31, IbMADS83 were highly expressed in fruit. In this study, the molecular basis of MADS-box genes of sweet potato was analyzed from various angles, and the effects of MADS-box genes on the growth and development of sweet potato were investigated, which may provide a certain theoretical basis for molecular breeding of sweet potato.